Maggot Frass Fertilizer: Effects on Productivity and Economic Efficiency in Organic Vegetable Farming - Nyoman Yudiarini; Meriam F. Sulit (Agro Bali : Agricultural Journal, 2025)
Maggot frass fertilizer derived from larvae waste processing represents an innovative organic fertilizer with significant potential for supporting sustainable agriculture implementation, particularly in organic vegetable commodities. This study aimed to analyze the technical effectiveness of maggot frass fertilizer application in organic vegetable cultivation and examine the economic efficiency of farming systems in Panji Village, Buleleng, Bali. Results demonstrated that maggot frass fertilizer application technically increased crop productivity by 15%. The study design has been clarified as a cross-sectional descriptive field study. Quantitative methods are used for effectiveness evaluation and business feasibility analysis, employing the R/C ratio. an average effectiveness value of 76.33% based on criteria including yield achievement, cost planning, and application dose appropriateness. Regarding economic efficiency, maggot frass reduced fertilizer costs by 29.73% with R/C ratios of 2.6 (non-organic) and 3.7 (organic), indicating high business feasibility. These findings suggest that maggot frass represents not only an effective agronomic innovation but also constitutes part of a sustainable agricultural approach based on local resources and principles of the circular economy. Therefore, institutional strengthening and policy support are required to enhance broader and more sustainable adoption of maggot frass technology.